Performance Comparison of UWB Single Balanced Schottky Diode Mixers for RF Front-End Applications in 3-10 GHz Band - Noor Azwan Shairi; Yahya Al-gumaei Mohammed; Zahriladha Zakaria; Maizatul Alice Meor Said; Mohamad Harris Misran; Zaghir Zobilah Abdullah Mohammed (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
This paper compares two single balanced mixer designs for ultra-wideband (UWB) of RF front-end at frequencies ranging from 3 to 10 GHz. The proposed mixer designs use two balun topologies for varying mixer performances. Thus, Design 1 incorporates a Coupled Line Balun and Design 2 incorporates a Branch Line Balun. Both designs make use of Skyworks' SMS7621 Schottky diodes, which have a low junction capacitance, and the Rogers RO4350B substrate, which has a dielectric constant of 3.48. The Coupled Line Balun (Design 1) offers a total length of 88 mm, whereas the Branch Line Balun (Design 2) creates a more compact structure with 48 mm. This paper's thorough analysis and measurements show each design's benefits and drawbacks in terms of circuit size and performance. The simulations and measurement results of both designs generally showed a conversion loss of less than 20 dB and LO-RF isolation of better than 50 dB.